Bladder Outlet Obstruction as a Cause for Late Total Flap Failure in Pelvic Reconstruction with a VRAM - Stein, Michael J.; Momtazi, Moein (Journal of Reconstructive Microsurgery Open, 2018)
Background A 67-year-old man presented with abrupt failure of a pedicled vertical rectus abdominus myocutaneous (VRAM) flap 13 days postoperatively.Methods The patient underwent pelvic reconstruction with a pedicled VRAM flap following sacral chordoma and abdominoperineal resection. The flap remained well perfused and viable until postoperative day 13, at which point the patient was noted to become systemically unwell with fever, chills, and abdominal pain. This clinically coincided with prompt arterial and venous insufficiency of the VRAM flap.Results Computed tomography of the abdomen was ordered to rule out a pelvic collection and revealed an inflated Foley catheter in the bulbar urethra. This was associated with marked distention of the bladder and bilateral hydronephrosis. Direct compression of the deep inferior epigastric pedicle by the bladder neck was noted.Conclusion The case highlights the importance of considering bladder outlet obstruction and subsequent distention as a cause of pedicle compression and VRAM flap failure following pelvic reconstruction.
Keywords: pelvic reconstruction; perineal reconstruction; pelvic exenteration; VRAM; abdominoperineal resection; flap failure